Stratigraphy, sedimentology, and palaeoenvironment of dinosaur-bearing Upper Cretaceous Zhengyang Formation in Zhengyang Basin, Chongqing, Southwest China - Hui Dai; Jun Wang; Liang-Dong Luo; Qian-Ru Wen; Su-Chin Chang; Yu Lin; Ming Xiao; Hai Xing (Palaeoworld, 2026)

Combined targeting poly (ADP-ribose) polymerase and receptor tyrosine kinase inhibits ovarian clear cell carcinoma progression through disrupted ribosome biogenesis - Chiao-Yun Lin; An-Shine Chao; Angel Chao; Ren-Chin Wu; Alice L. Yu; Chiung-Hui Fu; Yu-Chuan Teng; Ruby Yun-Ju Huang; Chyong-Huey Lai (Journal of Molecular Medicine, 2026)

Flexural bandgap of a metaplate carrying zigzag beam-mass systems - Jung-San Chen; Jie-Sheng Zheng; Yi-Chen Wu; Song-Rong Lin; Wei-Chang Li; Bhisham Sharma; Chin-Han Yang; Yu-Kai Lin (Engineering Structures, 2026)

Pyridoxine and valproic acid co-exposure induces ER-mediated calcium dysregulation and cardiac toxicity in zebrafish - Wei-Hsiang Chen; Po-Yuan Chen; Wen-Yu Chung; Tein-Yu Chiu; Wei-Ling Lin; Chen-Yu Huang; Hui-Hua Chang; Chin-Wei Huang; Bing-Hung Chen; Lin Kang; Tzu-Fun Fu (Chemico-Biological Interactions, 2026)

Artificial intelligence-related technologies for municipal solid waste management: A review and new insights from smart cities - Tachin Chin; Ying Fan; Chien-Liang Lin; Yu-Cheng Lin; Kuo-Ti Liao (Sustainable Cities and Society, 2026)

Late Holocene human-environment interactions on a small island of the Taiwan Strait - Ranjan Kumar Mohanty; Abdur Rahman; Yi-Chen Ho; Yu-Chen Lu; Cheng-Tao Lin; Hung-Chun Chao; Ling-Ho Chung; Chin-Yung Chao; Liang-Chi Wang (Quaternary International, 2026)

Matriptase proteolysis selectively drives disassembly and internalization of the claudin-7 complex while preserving E-cadherin - Yu-Ling A. Kao; He-Yu Huang; Yin S. Yu; Nanxi Huang; Ya-Chin Chan; Chen-Ray Lee; Michael D. Johnson; Chen-Yong Lin (Human Cell, 2026)

Long-term increases in urinary metals are associated with lipid peroxidative but not oxidative DNA damage in adolescents and young adults: A 10-year prospective cohort study - Chien-Yu Lin; Po-Chin Huang; Hui-Ling Lee; Ta-Chen Su (Environmental Pollution, 2026)

Efficient Underwater Image Super-Resolution via Learnable Color Conversion and Dual-Branch Mamba Network - Yu-Yang Lin; Wan-Jen Huang; Chia-Hung Yeh; Yi-Shiuan Yang; Chua-Chin Wang (Journal of Marine Science and Engineering, 2026)
Underwater image super-resolution plays an important role in marine exploration, as it aims to recover clearer and higher-resolution images from degraded low-resolution observations. However, in underwater environments, this task is particularly challenging due to non-uniform spectral attenuation and particle scattering. Underwater, red light fades quickly, leading to color distortion and loss of details. To address this while keeping the model lightweight, we propose a dynamic color-space network for single-image super-resolution. Traditional methods use fixed color conversion and cannot handle non-uniform attenuation well. We instead use a learnable module to adaptively obtain luminance (Y) and chrominance (CbCr) representations. Building upon this representation, we employ a highly efficient dual-branch architecture where the Y-channel features are processed using light Mamba blocks to capture spatial dependencies with linear complexity, while the CbCr-channel features are restored by a lightweight convolutional neural network. Finally, a lightweight residual model utilizing depth-wise separable convolutions (DSC), deformable convolutions, and pixel attention mechanisms is introduced to refine the features and suppress artifacts. Experimental results demonstrate that while achieving competitive restoration quality, the proposed method drastically reduces computational complexity and parameter count compared to other large-scale models. This balance between visual quality and computational efficiency makes the proposed method well-suited for real-time deployment on resource-constrained autonomous underwater vehicles (AUVs).

Enhancing environmental stress tolerance of Saccharomyces cerevisiae by deletion of NTH1 and FKS3: Implications for beer brewing - Chih-Yuan Tan; Huan-Yu Lin; Tsung-Tang Chen; Ying-Ta Shih; Yun-Chin Chung (International Journal of Food Microbiology, 2026)

Formaldehyde activates the RUNX1–ISX axis to promote leukemic reprogramming, a pathway associated with poor prognosis in pediatric B-ALL - Pei-Chin Lin; Li-Ting Wang; Li-Heng Ye; Pin-Ying Tseng; Pei-Hsien Huang; Wan-Yi Hsu; Yu-Mei Liao; Shyh-Shin Chiou; Shih-Hsien Hsu (Environmental Pollution, 2026)

Applying the iRIC Morpho2DH model to determine the effectiveness of check dams against debris flows - Zheng-Yi Feng; Philipp Marr; Tien-Chun Hsu; Ping-Hsuan Kuo; Yu-Po Lin; Ming-Chih Chuang; Ching-Mao Huang; Edoardo Carraro; Su-Chin Chen; Chen-Yu Chen; Thomas Glade (Landslides, 2026)

Middle Eocene arc magmatism from Armenia with new insights into tectonic evolution of the Arabia-Eurasia collision zone - Yu-Chin Lin; Kwan-Nang Pang; Ghazar Galoyan; Rafael Melkonyan; Hao-Yang Lee; Ching-Hua Lo; Jin-Hui Yang; Sun-Lin Chung (Lithos, 2026)

Safety and toxicity assessment of Lactobacillus salivarius AP-32 with Probiotic potential in vivo and in vitro - Yu-Hsuan Chin; Yi-Wen Chen; Yen-Yu Huang; Ching-Min Li; Jia-Hung Lin; Yi-Wei Kuo; Chen-Yu Chen; Yen-Feng Lee; Cian-Dai Ciou; Ko-Chiang Hsia; Shin-Yu Tsai; Hsieh-Hsun Ho (Food and Chemical Toxicology, 2026)

Intelligent circuit exercise training improves platelet mitochondrial bioenergetic efficiency in sedentary men - Ai Yin Lim; Chi-Yao Chiang; Yu-Ting Lin; Chih-Chin Hsu; Jong-Shyan Wang (European Journal of Applied Physiology, 2026)

Evaluation of the effectiveness of indigenous entomopathogenic fungi for controlling chilli thrips (Scirtothrips dorsalis Hood) in blueberry under greenhouse conditions - Hsin-Yu Lin; Yi-Ju Chen; Kusum Mushyakhwo; Chin-Mu Chen; Yu-Shin Nai (BioControl, 2026)

Rapid microfluidic sample preparation for mass spectrometric analysis of wild-type and mutant BRAF protein - Yen-Heng Lin; Heng-Yun Chang; Chia-Chun Wu; Yung-Chin Hsiao; Ying-Hao Wen; Jau-Song Yu (Analytica Chimica Acta, 2026)

An accelerated meshfree computational framework with machine learning classification for multi-phase modeling of landslide - Kuan-Chung Lin; Yih-Chin Tai; Po-Han Lee; Hock-Kiet Wong; Yanran Wang; Yu-Shu Lu; Jiun-Shyan Chen (Computers and Geotechnics, 2026)

Sonofoam: An ultrasound-responsive foam for broad pleural coverage and sonoporation-enhanced drug delivery in pleurodesis - Hsin-Yi Lin; Wei-Chih Liao; Yun-Chieh Lin; Hsin-Chin Li; Min-Yu Tsou; Bo-Tai Cheng; Yu-Nan Huang; Ulziijargal Sukhbat; Chun-Yi Chiang; Chi-Fen Chuang; Zong-Han Hsieh; Chih-Yen Tu; et al. (Chemical Engineering Journal, 2026)

Optical properties of dissolved organic matter play pivotal roles in mediating trace metal forms in a mangrove-dominated tidal estuary - Keisuke Nakayama; Meng-Chi Hung; Chih-Yu Chiu; Sen-Lin Tang; Mei-Li Hsueh; Chin-Ching Wu; I-Hao Hung; Ya-Hsin Liu; Jeng-Wei Tsai (Marine Pollution Bulletin, 2026)

Association between urinary metabolites of 1,3-butadiene and toluene exposure with kidney function indices in Taiwanese school-aged children living near a petrochemical complex - Po-Keng Cheng; Vinoth Kumar Ponnusamy; Wei-Hong Lin; Jeganathan Chinnadurai; Pei-Chien Tsai; Cai-Yu Chen; Wan-Ting Chang; Po-Chin Huang (Environmental Pollution, 2026)

Release of microplastics from polyvinyl chloride pipes: Using accelerated aging by ozonation, chlorination and heating to assess the release potential - Yu-Teng Ji; Yi-Chin Cho; Jenyuk Lohwacharin; Yi-Pin Lin (Journal of Environmental Chemical Engineering, 2025)

In-situ control of biohythane production in electro-anaerobic digestion - Chao-Chin Chang; Yu-Wen Lin; Chang-Ping Yu; Zhen He (Chemical Engineering Journal, 2025)

Using an acidic vesicle tracer to identify potential bacterivores in coastal waters of the subtropical Western Pacific Ocean - Yun-Chi Lin; Yu-Chen Lin; Kuo-Ping Chiang; Chien-Pang Chin; Wen-Chen Chou (Frontiers in Marine Science, 2025)
Bacterivores play a key role in transferring energy through microbial food webs and are broadly classified as heterotrophic or mixotrophic based on the presence of inherent chloroplasts. Mixotrophs, especially in low-latitude regions, have recently gained attention due to their dual roles as primary producers and bacterial grazers, which enable them to thrive in nutrient-poor, stratified waters where traditional autotrophs or heterotrophs may be less competitive. This study investigated the composition of bacterivores in the coastal waters of northeastern Taiwan during the warm season (July and August 2022). A combination of LysoTracker staining, flow cytometry sorting, and 18S rRNA gene amplicon sequencing was used to rapidly identify heterotrophic and mixotrophic nanoflagellates (HNFs and MNFs, respectively) based on chloroplast autofluorescence. The dominant eukaryotic lineages included Alveolata, Stramenopiles, Opisthokonta, Chlorophyta, and Rhizaria. HNFs were primarily composed of MAST clades, choanoflagellates (Opisthokonta), Telonemia, and Radiolaria, while MNFs included cryptophytes, haptophytes, and chlorophytes such as Mamiella , Mantoniella and Tetraselmis , as well as stramenopiles like Dictyochophyceae and Chrysophyceae. Notably, several non-motile chlorophytes, including Chloropicon and members of Pycnococcaceae, were identified as potential bacterivores based on Lysotracker signals; however, their phagotrophic capability requires further confirmation in future studies. Despite the limitations of LysoTracker-based methods, this study reveals previously overlooked mixotrophic diversity and highlights the need for further validation. These findings advance our understanding of carbon flow and microbial dynamics in subtropical marine ecosystems under changing environmental conditions.

Geotechnical reconnaissance of Hualien Port after the 2024 ML 7.2 hualien earthquake - Hsuan-Chih Yang; Chun-Jia Huang; Yung-Yen Ko; Kuan-Yu Chen; Chi-Chin Tsai; Chun-Hung Lin; Yu Wei Hwang; Min-Chien Chu; Yu-Syuan Jhuo; Yu-Ting Hsueh; Shodai Okano; LeeYi Wang; et al. (Soil Dynamics and Earthquake Engineering, 2025)

Microfluidic device for high-throughput cancer drug screenings - Po-Hsun Chen; Lin-Yu Wang; Chia-Yuan Chang; Yuh-Shiuan Chien; Yu-Chia Su; Chi-Kuang Wang; Kuang-Chong Wu; Hsian-Jean Chin; Chien-Fu Chen (Chemical Engineering Journal, 2025)

Targeting neuroblastoma with 3β,5α-tetrahydrocorticosterone: Activation of aryl hydrocarbon receptor inhibits tumor growth, metastasis, and stemness while promoting neural differentiation - Zhu-Qian Wen; Wen-Ming Hsu; Chien-Chun Chiou; Farhan Azhwin Maulana; Chia-Hwa Chang; Jie-Ming Huang; Zhi-Kai Yu; Chien-Chin Chen; Neng-Yu Lin; Chun-FA. Tsai; Jheng-Siou Lai; Yue-Ling Chen; et al. (Chemico-Biological Interactions, 2025)

Perhydroxylated benzoquinoid covalent triazine framework for ultra-high-density lithium-ion storage - Nhu T.H. Luu; Rajeshkumar Anbazhagan; Alexander S. Ivanov; Sung-En Lin; Chia-Hsin Chang; Chen-Yu Hung; Ilja Popovs; Jui-Chin Lee; Teng-Hao Chen; Watchareeya Kaveevivitchai (Chemical Engineering Journal, 2025)

Unveiling Unusual Ecofunctional Traits of Endozoicomonas Species Through Comprehensive Comparative Genomics - Sim Lin Lim; Ching‐Hsiang Chin; Yu‐Jing Chiou; Ming‐Tsung Hsu; Pei‐Wen Chiang; Hsing‐Ju Chen; Yung‐Chi Tu; Wen‐Shyong Tzou; Sen‐Lin Tang (Environmental Microbiology, 2025)
Endozoicomonas is an omnipresent marine bacterial genus, associated with various marine organisms, that contributes to host health, nutrient cycling and disease resistance. Nonetheless, its genomic features remain poorly characterised due to a paucity of high‐quality genomes. In this study, we sequenced 5 novel Endozoicomonas strains and re‐sequenced 1 known strain to improve genomic resolution. By integrating these 6 high‐quality genomes with 31 qualified published genomes, our pan‐genomic analysis revealed variation in genetic traits among clades. Notably, Endozoicomonas lacks quorum‐sensing capabilities, suggesting resistance to quorum quenching mechanisms. It also lacks the capacity to synthesise and transport vitamin B12, indicating that it does not supply this nutrient to holobionts. Remarkably, Endozoicomonas genomes encode 92 identified giant proteins (15–65 kbp). These proteins cluster into three major groups associated with antimicrobial peptide synthesis, exotoxin production and cell adhesion. Additionally, we found that Endozoicomonas has acquired prophages from diverse sources via infection or other types of gene transfer. Notably, CRISPR‐Cas sequences suggest evolutionary trajectories independent of both prophage acquisition and phylogenetic lineage, implying potential geographic influences or environmental pressures. This study provides new insights into the genomic diversity of Endozoicomonas and its genetic adaptations to diverse hosts.

Navigating crowds: Reconsidering visitor recreational experience and crowding preference for a forest park in Taiwan - Wan-Yu Liu; Chin-Chun Yen; Rachel S.K. Lee; Chun-Cheng Lin (Forest Policy and Economics, 2025)

Mercury flows in a cement plant adopting circular economy policies - Liang Yu Chen; Chia Chi Hsu; Chin Lung Lin; Ming Lun Lu; Hung Lin Chiang; Moo Been Chang (Waste Management, 2025)

Building with nature: Morphological spatial pattern of green infrastructure in urban heat mitigation - Bau-Show Lin; Yu-Hua Tsai; Han-Chin Chang; Chin-Chung Yu; Cheng-I Hsieh (Building and Environment, 2025)

Spatial patterns of essential fish habitats in the western Taiwan coast - Yu-Jia Lin; Chien-Cheng Lai; Hsu-Sen Chen; Tsu-Chun Chen; Kuo-Shu Chen; Norhafiz Hanafi; Pei-Jie Meng; Ying-Chin Fang; Chiee-Young Chen; Hsin-Ming Yen; Meng-Hsien Chen (Estuarine, Coastal and Shelf Science, 2025)

Development of an alkali-producing bioelectrochemical system for sewage-polluted seawater: nutrient removal, scalant mitigation, and resource recovery - Chao-Chin Chang; Chieh-Yun Wu; Jia-Zhe Jiang; Chen-An Hsu; Chang-Ping Yu; Yi-Li Lin (Journal of Water Process Engineering, 2025)

BTEX exposure and metabolite levels in Taiwan schoolchildren near petrochemical areas - Wei-shan Chin; Ching-chun Huang; Yu-cheng Chen; Jing-fang Hsu; Chih-Da Wu; Pinpin Lin; Pau-chung Chen; Yue Leon Guo (International Journal of Hygiene and Environmental Health, 2025)

Correlation between the utilization of sodium-glucose cotransporter-2 (SGLT2) inhibitors and the risk of dementia: a nationwide population-based study in Taiwan - Wu-Lung Chuang; Stella Chin-Shaw Tsai; Yi-Chun Yang; Tsai-Ling Hsieh; Heng-Jun Lin; Yu-Han Huang; Fuu-Jen Tsai; Kuang-Hsi Chang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Origin and metamorphism of ophiolitic serpentinites from the Yuli belt, eastern Taiwan: new findings and tectonic implications - Dominikus Deka Dewangga; Chin-Ho Tsai; Yoshiyuki Iizuka; Ilona Talvikki Sakaguchi; Yui Kouketsu; Sun-Lin Chung; Chi-Yu Lee; Wen-Yen Chang; Huei-Fen Chen (International Geology Review, 2025)

Knockout of dead end 1 by CRISPR/Cas9 leads to loss of germ cells and male-biased sex development in freshwater angelfish (Pterophyllum scalare) - Wai-Kwan Chu; Shih-Chin Huang; Ching-Fong Chang; Yu-Ho Lin; Jen-Leih Wu; Hong-Yi Gong (Aquaculture, 2025)

Small intestine-residing probiotics suppress neurotoxic bile acid production via extracellular vesicle-mediated inhibition of Clostridium scindens - Wei-Leng Chin; Bao-Hong Lee; Qiao-Yu Hsu; Chih-Yao Hou; Ming-Chyi Pai; Chi-Wei Lin; Wei-Hsuan Hsu (Food Research International, 2025)

Kirenol ameliorates endotoxin-induced acute lung injury by inhibiting the ERK and JNK phosphorylation–mediated NFκB pathway in mice - Frank Cheau-Feng Lin; Shih-Pin Chen; Sheng-Chien Lin; Ching-Chi Tseng; Stella Chin-Shaw Tsai; Yu-Hsiang Kuan (Inflammopharmacology, 2025)

Allopatric Speciation and Interspecific Gene Flow Driven by Niche Conservatism of Diploderma Tree Lizards in Taiwan - Tzong‐Han Lin; Zong‐Yu Shen; Ming‐Hsun Chou; Pei‐Wei Sun; Chin‐Chia Shen; Jen‐Pan Huang; Si‐Min Lin (Molecular Ecology, 2025)
Allopatric speciation is a widely accepted hypothesis for species distributed across geographic barriers. Meanwhile, niche conservatism, the tendency of species to retain their ancestral ecological traits, helps reinforce genetic differentiation by stabilising species distributions over time and reducing the role of competition in shaping range boundaries. In contrast, hybridisation can occur at the edges of distribution after secondary contact following climatic or geological events, leading to a reduction in genetic divergence between divergent lineages. In this study, we investigated the role of geographic barriers, niche conservatism and gene flow in the speciation history of Diploderma species in Taiwan, where geographically distinct taxa share similar environmental preferences. By using ddRAD‐seq data, seven distinct genetic clusters were identified with two putatively new cryptic species in D. brevipes and D. polygonatum . Most sister species pairs share similar climatic niches based on niche equivalency and similarity tests. We further detected significant historical gene flow between lineages of D. brevipes and D. polygonatum , where secondary contact might have occurred because of palaeoclimate changes and historical demographic expansion. Our results demonstrate that niche conservatism does not always act in concert to strengthen the result of allopatric speciation; instead, it may also lead to gene flow between divergent lineages following secondary contact. On the other hand, postdivergence gene flow may be a creating force generating phenotypic diversity in sexually selected traits in our study system. The underestimated species diversity of Diploderma in Taiwan requires further taxonomic work in the future.

Genetic Analysis of Polyunsaturated Fatty Acids Biosynthesis Pathway Determines Four Distinct Thraustochytrid Types - Sou‐Yu Cheng; Yi‐Jing Chen; Hsiu‐Chin Lin; Hsin‐Yang Chang; Ming‐Der Huang (Environmental Microbiology, 2025)
Thraustochytrids, diverse marine unicellular protists encompassing over 10 recognised genera, are renowned for synthesising polyunsaturated fatty acids (PUFAs), with content and composition varying substantially across genera. While PUFAs are known to be produced via PUFA synthase (PUFA‐S) and/or elongase/desaturase (ELO/DES) pathways, the distinctions in genes involved remain unexplored. This study analysed PUFA biosynthetic genes in 19 thraustochytrid strains across six genera, categorising them into four types. Type I exclusively utilises the ELO/DES pathway, Type II employs both PUFA‐S and complete ELO/DES pathways, while Types III and IV primarily rely on PUFA‐S, with Type III lacking the canonical Δ9 desaturase and Type IV missing most desaturase and elongase enzymes. Notably, the Δ9 desaturase and ATP‐citrate lyase ( ACLY ) are exclusive to Types I and II, while β‐carotene hydroxylase ( CrtZ ) is absent in these types. ACLY absence suggests alternative acetyl‐CoA supply pathways in Types III and IV, whereas CrtZ absence implies either a lack of specific xanthophylls or alternative biosynthetic pathways in Types I and II. Synteny analysis revealed conserved genomic organisation of PUFA biosynthetic genes, indicating a shared evolutionary trajectory. This study provides insights into the genetic diversity underlying PUFA biosynthesis in thraustochytrids, while proposing putative evolutionary pathways for the four lineages.

Proximity to petrochemical industry and risk of childhood asthma occurrence - Shih-Chun Pan; Wei-Shan Chin; Ching-Chun Huang; Yu-Cheng Chen; Chih-Da Wu; Chin-Yu Hsu; Pinpin Lin; Pau-Chung Chen; Yue Leon Guo (International Journal of Hygiene and Environmental Health, 2025)

Safety evaluation of Limosilactobacillus fermentum PS150 for use as a commercial psychobiotic - Li-Hao Cheng; Chien-Chen Wu; Chin-Lin Huang; Yu-Hsuan Wei; Pei-Jun Wen; Shih-Hau Chiu; Chien-Chi Chen; Ching-Ting Lin; Po-Lin Liao (Food and Chemical Toxicology, 2025)

Optimizing sediment control by adjusting the relative spacing between trusses/beams in an open-type check dam - Hung-En Chen; Tzu-Yu Chen; Ya-Lin Zheng; Yen-Yu Chiu; Su-Chin Chen (Landslides, 2025)

Recent progress on triterpenoid derivatives and their anticancer potential - Zi-Xuan Zhao; Qiong-Yu Zou; Ying-Hong Ma; Susan L. Morris‐Natschke; Xiang-Yuan Li; Lin-Chun Shi; Guo-Xu Ma; Xu‐Dong Xu; Mei‐Hua Yang; Zi-Jian Zhao; Yuan-Xiang Li; Jing Xue; et al. (Phytochemistry, 2025)

ω-9 monounsaturated fatty acids in Sapindus mukorossi seed oil enhance calcium deposition expression of Wharton’s jelly mesenchymal stem cells - Yu-Xuan Huang; Yen-Chung Lin; Chin-Kai Lin; Haw-Ming Huang (Tissue and Cell, 2024)

The impact of cooking methods on the physical, sensory, and nutritional quality of fish - Sook Chin Chew; Yu Hsuan How; Lee Sin Chang; Choon Hui Tan; Kalvin Meng Jun Chuo; Stephenie Yoke Wei Wong; Pascal Degraeve; Kar Lin Nyam (International Journal of Gastronomy and Food Science, 2024)

Effect of multi-processing technologies on the quality of sweet potato starch and associated starch pearl products - Min-Yu Lan; Jer-An Lin; Sheng-Yi Chen; Gow-Chin Yen (Food Bioscience, 2024)

Validation of the constitution in Chinese medicine questionnaires with the newly developed blood-vacuity category: a rare Taiwanese case study - Ting-Yu Huang; Shi-Chen Ou; Wei-Te Huang; Yu-Chuan Lin; Hao-Hsiu Hung; Chin-Wei Chang; Kai-Yuan Hsiao; Yi-Wei Kao; Chien-Hua Wu; Wei-Shan Chang; Ben-Chang Shia; Sheng-Teng Huang (Advances in Traditional Medicine, 2024)

Systematic establishment of the relationship between skin absorption and toxicity of furanoids via in silico, in vitro, and in vivo assessments - Yin-Ku Lin; Chien-Yu Hsiao; Chih-Jung Chen; Ahmed Alalaiwe; Chin Lee; Tse-Hung Huang; Jia-You Fang (Environmental Research, 2024)

Long non-coding RNA FKSG29 regulates oxidative stress and endothelial dysfunction in obstructive sleep apnea - Yung-Che Chen; Po-Yuan Hsu; Mao-Chang Su; Yung-Lung Chen; Ya‐Ting Chang; Chien-Hung Chin; I.-Chun Lin; Yu-Mu Chen; Ting-Ya Wang; Yong-Yong Lin; Chiu-Ping Lee; Meng-Chih Lin; et al. (Molecular and Cellular Biochemistry, 2024)

Structure-Functional Activity of Pyrone Derivatives for Inhibition of Barnacle Settlement and Biofilm Formation - Mo Aqib Raza Khan; Bo-Wei Wang; Hsiu-Chin Lin; Yu-Liang Yang; Chih-Chuang Liaw (Marine Biotechnology, 2024)

Biofunctionalized hydrogel composed of genipin-crosslinked gelatin/hyaluronic acid incorporated with lyophilized platelet-rich fibrin for segmental bone defect repair - Er-Yuan Chuang; Yi-Cheng Lin; Yu-Min Huang; Chih-Hwa Chen; Yi-Yen Yeh; Lekha Rethi; Yu-Jen Chou; Pei-Ru Jheng; Jen-Ming Lai; Chang-Jung Chiang; Chin-Chean Wong (Carbohydrate Polymers, 2024)

Streptococcus taoyuanensis sp. nov., a Novel Species Isolated from a Patient with Bacteremia - Chien-Yu Lee; Chin-Kan Chan; Yi-Sheng Chen; Yun-Shien Lee; Shih-Ting Lin; Yu-Chung Chang; Hui-Chung Wu; Jia-rong Zhang; Hong-yu Chen; Li-Ting Wang (Current Microbiology, 2024)

Associations among global long interspersed nuclear element-1 DNA methylation, metal exposure, and chronic kidney disease - Yu-Mei Hsueh; Mei-Chieh Chen; Ying-Chin Lin; Chih-Yin Wu; Horng-Sheng Shiue; Sheng-Lun Hsu; Hsi-Hsien Chen; Ya-Li Huang (Archives of Toxicology, 2024)

The impact of flooding from the Minjiang River on the succession of harmful algal blooms (HABs) caused by diatoms in China's offshore waters - Yun-Chi Lin; Ya-Han Nien; Kuo-Ping Chiang; Chien-Pang Chin; Wei-Ting Chen; Gwo-Ching Gong; Wen-Chen Chou; Chi-Yu Shih; Kuo-Shu Chen (Marine Pollution Bulletin, 2024)

Underwater Image Enhancement Based on Light Field-Guided Rendering Network - Chia-Hung Yeh; Yu-Wei Lai; Yu-Yang Lin; Mei-Juan Chen; Chua-Chin Wang (Journal of Marine Science and Engineering, 2024)
Underwater images often encounter challenges such as attenuation, color distortion, and noise caused by artificial lighting sources. These imperfections not only degrade image quality but also impose constraints on related application tasks. Improving underwater image quality is crucial for underwater activities. However, obtaining clear underwater images has been a challenge, because scattering and blur hinder the rendering of true underwater colors, affecting the accuracy of underwater exploration. Therefore, this paper proposes a new deep network model for single underwater image enhancement. More specifically, our framework includes a light field module (LFM) and sketch module, aiming at the generation of a light field map of the target image for improving the color representation and preserving the details of the original image by providing contour information. The restored underwater image is gradually enhanced, guided by the light field map. The experimental results show the better image restoration effectiveness, both quantitatively and qualitatively, of the proposed method with a lower (or comparable) computing cost, compared with the state-of-the-art approaches.

In vitro and in vivo protective potential of quercetin-3-glucuronide against lipopolysaccharide-induced pulmonary injury through dual activation of nuclear factor-erythroid 2 related factor 2 and autophagy - Pei-Rong Yu; Chiao-Yun Tseng; Cheng-Chin Hsu; Jing-Hsien Chen; Hui-Hsuan Lin (Archives of Toxicology, 2024)

Streptococcus taonis sp. nov., a novel bacterial species isolated from a blood culture of a patient - Chien-Yu Lee; Chin-Kan Chan; Momoko Chida; Mika Miyashita; Yun-Shien Lee; Hui-Chung Wu; Yu-Chung Chang; Wen-Ting Lin; Yi-Sheng Chen (Archives of Microbiology, 2024)

Impact of occupational noise exposure on the hearing level in hospital staffs: a longitudinal study - Tang-Chuan Wang; You-Cheng Yu; Alan Hsu; Jia-Yi Lin; Yung-An Tsou; Chiu-Shong Liu; Kai-Jen Chuang; Wen-Chi Pan; Chin-An Yang; Sung-Lin Hu; Chien-Yi Ho; Tzu-Liang Chen; et al. (Environmental Science and Pollution Research, 2024)

Heteronemin promotes iron-dependent cell death in pancreatic cancer - Gizem Kaftan; Mümin Alper Erdoğan; Mohamed El-Shazly; Mei-Chin Lu; Shou-Ping Shih; Hung-Yu Lin; Luciano Saso; Güliz Armagan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

The two-back task leads to activity in the left dorsolateral prefrontal cortex in schizophrenia patients with predominant negative symptoms: a fNIRS study and its implication for tDCS - Chin-Chao Ma; Yen-Yue Lin; Yong-An Chung; Sonya Youngju Park; Cathy Chia-Yu Huang; Wei-Chou Chang; Hsin-An Chang (Experimental Brain Research, 2024)

Electro-forward osmosis through a titanium-dioxide-modified membrane to enhance aquaculture wastewater recovery - Yi-Li Lin; Nai-Yun Zheng; Yu-Sheng Chen; Chao-Chin Chang (Desalination, 2024)

Effects of vitamin D and zinc deficiency in acute and long COVID syndrome - Kuang-Yu Chen; Chin-Kuo Lin; Ning-Hung Chen (Journal of Trace Elements in Medicine and Biology, 2023)

Practically Feasible Sensor-Embedded Kinetic Assessment Piano System for Quantifying Striking Force of Digits During Piano Playing - Kuan-Yin Lai; Chieh-Hsiang Hsu; Yu-Chen Lin; Chung-Hung Tsai; Cheng-Feng Lin; Li-Chieh Kuo; Fong-Chin Su (Journal of Medical and Biological Engineering, 2023)
Purpose Understanding the pathogenesis of playing-related hand disorders through investigations based on coordination and biomechanical perspectives is indispensable. This study aimed to establish a sensor-embedded kinetic assessment piano system (SeKAPS) and conduct reliability and validity tests for this system. In addition, the differences in digit coordination between professional pianists and non-musicians were investigated. Methods Twelve subminiature load cells were embedded in the middle of the 12 corresponding keys of an upright piano. A customized calibrated system with a load cell was used to establish the criterion-related validity of the SeKAPS. The reliability of the SeKAPS was determined by 22 volunteer pianists. The other ten professional pianists and ten non-musicians were recruited to indicate the feasibility of the SeKAPS to distinguish the performing differences between groups. Results The R 2 values of regression analyses for the load cells were 0.993–0.999 ( p < 0.001), indicating high validity. The ICC values of the modified keys were 0.82–0.93, indicating high reliability. The results indicate that SeKAPS is accurate in detecting the striking force of digits during piano playing. Significant differences existed in the mean peak force and mean CVs of the peak force of the specific digits between the two groups. The results showed differences in finger control strategies between the pianists and non-musicians. Conclusion The SeKAPS may provide a valuable assessment for assisting pianists in understanding digit force control and movement strategies to achieve efficient digit coordination.

Associations between paraben exposure, thyroid capacity, homeostasis and pituitary thyrotropic function in the general Taiwanese: Taiwan Environmental Survey for Toxicants (TEST) 2013 - Po-Chin Huang; Hsin-Chang Chen; Shih-Hao Leung; Yu-Jung Lin; Han-Bin Huang; Wan-Ting Chang; Hsin-I. Huang; Jung-Wei Chang (Environmental Science and Pollution Research, 2023)

The Critical Role of Equilibrative Nucleoside Transporter-2 in Modulating Cerebral Damage and Vascular Dysfunction in Mice with Brain Ischemia-Reperfusion - Hui-Ling Chiang; Kuo-Chen Wu; You-Yin Chen; Chin-Jui Ho; Han-Lin Wang; Yu-Hua Fu; Wen-Yu Chen; Chun-Jung Lin (Pharmaceutical Research, 2023)

Rapid identification and monitoring of cooking oil fume-based toxic volatile organic aldehydes in lung tissue for predicting exposure level and cancer risks - Karthikeyan Prakasham; Swapnil Gurrani; Chia-Fang Wu; Ming-Tsang Wu; Tusty-Jiuan Hsieh; Chiung-Yu Peng; Po-Chin Huang; Anbarasu Krishnan; Pei-Chien Tsai; Yu-Chia Lin; Bongee Tsai; Yuan-Chung Lin; et al. (Chemosphere, 2023)

High-performance peptide and disulfide mapping by direct injection of intact proteins using on-line coupled UV-liquid chromatography microdroplet mass spectrometry (UVLC-MMS) - Chin-Ming Kuo; Hung-Hsiang Jen; Fung-Yu Chen; Mohsen Akbarian; Tai-Hong Ou; Kang-Yu Liu; Jung-Lee Lin; Shu-Hui Chen (Analytica Chimica Acta, 2023)

Estimating the daily average concentration variations of PCDD/Fs in Taiwan using a novel Geo-AI based ensemble mixed spatial model - Chin-Yu Hsu; Tien-Wei Lin; Jennieveive B. Babaan; Aji Kusumaning Asri; Pei-Yi Wong; Kai-Hsien Chi; Tuan Hung Ngo; Yu-Hsuan Yang; Wen-Chi Pan; Chih-Da Wu (Journal of Hazardous Materials, 2023)

Sublethal effects of methylmercury on lateral line sensory and ion-regulatory functions in zebrafish embryos - Giun-Yi Hung; Yu-Chin Pan; Jiun-Lin Horng; Li-Yih Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Toward ultra-high efficiency tandem OLEDs: Benzothiazole-based bipolar hosts and specific device architectures - Jui-Ming Wang; Ting-Chun Lee; Chia-Chen Chung; Wun-Yu Chen; Sih-Yu Wu; Yan-Ding Lin; Yuan Jay Chang; Chin-Wei Lu; Chih-Hao Chang (Chemical Engineering Journal, 2023)

Copper nanoparticles encapsulated in reduced graphene oxide electrode (CuxrGO1-x) for the electrochemical quantification of metformin in water - Yu-Jen Shih; Yu-Qiao Su; Wei-Hsiang Chen; Sheng-Kai Lin; Yi-Chun He; Chin-Pao Huang (Chemical Engineering Journal, 2023)

Ultra-sensitive determination of Ochratoxin A in coffee and tea samples using a novel semi-automated in-syringe based coagulant-assisted fast mycotoxin extraction (FaMEx) technique coupled with UHPLC-MS/MS - Karthikeyan Prakasham; Swapnil Gurrani; Jentaie Shiea; Ming-Tsang Wu; Chia-Fang Wu; Yu-Chia Lin; Bongee Tsai; Po-Chin Huang; Gangadhar Andaluri; Vinoth Kumar Ponnusamy (Food Chemistry, 2023)

Regulating energy gap in Ir-based ionic complexes to generate near-infrared emissions: Application in solid-state light-emitting electrochemical cells - Yan-Ding Lin; Pei-Wan Hsiao; Wun-Yu Chen; Sih-Yu Wu; Wei-Min Zhang; Chin-Wei Lu; Hai-Ching Su (Chemical Engineering Journal, 2023)

Simultaneous biomonitoring of volatile organic compounds’ metabolites in human urine samples using a novel in-syringe based fast urinary metabolites extraction (FaUMEx) technique coupled with UHPLC-MS/MS analysis - Swapnil Gurrani; Karthikeyan Prakasham; Po-Chin Huang; Ming-Tsang Wu; Chia-Fang Wu; Yu-Chia Lin; Bongee Tsai; Anbarasu Krishnan; Pei-Chien Tsai; Vinoth Kumar Ponnusamy (Chemosphere, 2023)

p-y based approach to predicting the response of monopile embedded in soft clay under long-term cyclic loading - Chi-Chin Tsai; Yu-Pai Li; Sheng-Hui Lin (Ocean Engineering, 2023)

Cardiac-specific overexpression of insulin-like growth factor II receptor-α interferes with the regulation of calcium homeostasis in the heart under hyperglycemic conditions - Shang-Yeh Lu; Bruce Chi-Kang Tsai; Dao Van Thao; Chin-Hu Lai; Michael Yu-Chih Chen; Wei-Wen Kuo; Chia-Hua Kuo; Kuan-Ho Lin; Dennis Jine-Yuan Hsieh; Chih-Yang Huang (Molecular Biology Reports, 2023)

Transition of carbon-nitrogen coupling under different anthropogenic disturbances in subtropical small mountainous rivers - Li-Chin Lee; Gabriele Weigelhofer; Thomas Hein; Shin-Chien Chan; Ying-San Liou; Chien-Sen Liao; Fuh-Kwo Shiah; Yu-Lin Yu; Tsung-Yu Lee; Jr-Chuan Huang (Science of The Total Environment, 2023)

The effect of isovitexin on lipopolysaccharide-induced renal injury and inflammation by induction of protective autophagy - Chiao-Yun Tseng; Pei-Rong Yu; Cheng-Chin Hsu; Hui-Hsuan Lin; Jing-Hsien Chen (Food and Chemical Toxicology, 2023)

Attentional focus effect on dual-task walking in Parkinson’s disease with and without freezing of gait - Yu-An Chen; Ruey-Meei Wu; Chen-Hsing Sheu; Chin-Hsien Lin; Cheng-Ya Huang (GeroScience, 2023)

A low-cost eco-friendly fast drug extraction (FaDEx) technique for environmental and bio-monitoring of psychoactive drug in urban water and sports-persons’ urine samples - Swapnil Gurrani; Karthikeyan Prakasham; Jess Lim Zii Ying; Jentaie Shiea; Yi-Jia Ku; Yu-Chia Lin; Po-Chin Huang; Gangadhar Andaluri; Kung-Che Lee; Vinoth Kumar Ponnusamy (Environmental Research, 2023)

Novel fast pesticides extraction (FaPEx) strategy coupled with UHPLC-MS/MS for rapid monitoring of emerging pollutant fipronil and its metabolite in food and environmental samples - Raghavendra Rao Pasupuleti; Yi-Jia Ku; Tseng-Yu Tsai; Hung-Ta Hua; Yu-Chia Lin; Jentaie Shiea; Po-Chin Huang; Gangadhar Andaluri; Vinoth Kumar Ponnusamy (Environmental Research, 2023)

Using cluster algorithms with a machine learning technique and PMF models to quantify local-specific origins of PM2.5 and associated metals in Taiwan - Chin-Yu Hsu; Jhy-Charm Soo; Sheng-Lun Lin; Chih-Da Wu; Kai Hsien Chi; Wen-Chang Hsu; Chun-Chieh Tseng; Yu-Cheng Chen (Environmental Pollution, 2023)

Equilibrative Nucleoside Transporter 1 is a Target to Modulate Neuroinflammation and Improve Functional Recovery in Mice with Spinal Cord Injury - Kuan-Yu Chen; Chiao-Shin Lu; Cheng-Yoong Pang; Chin-Jui Ho; Kuo-Chen Wu; Hsiu-Wei Yang; Hsin-Lin Lai; Yijuang Chern; Chun-Jung Lin (Molecular Neurobiology, 2023)

AIoT-Based Ergometer for Physical Training in Frail Elderly with Cognitive Decline: A Pilot Randomized Control Trial - Chih-Chun Lin; Li-Chieh Kuo; Yu-Sheng Lin; Chia-Ming Chang; Fang Wen Hu; Yi-Jing Chen; Chun-Tse Lin; Fong-Chin Su (Journal of Medical and Biological Engineering, 2022)
Purpose Reduced physical activity is reported in the elderly, especially in institutional residents. Institutionalized older adults exhibit a high prevalence of frailty. In this work, we developed an artificial intelligence of things (AIoT)-based feedback assistive strengthening ergometer (AIFASE), for the physical strengthening of the elderly with intelligent assistance. Methods We conducted a 12-week intervention in a long-term care facility. In total, 16 participants (84.38 ± 6.0 years; 4 males and 12 females) were recruited with 1:1 randomization of exercise to control groups. The muscle strength of the lower extremities, timed up and go test (TUG), and Short-form Physical Performance Battery (SPPB) of the participants were measured. The AIFASE system allows the clinical staff to record the personal physical performance of the elderly and generates personalized exercise prescriptions accordingly. AIFASE also displays the current usage status of all ergometers and the users’ physiological conditions. The algorithms were developed to generate warning alerts when the training workload was too large by personal physiological detection. AIFASE automatically customized the exercise prescription according to the user’s exercise performance. Results After a 12-week AIFASE intervention, the intervention group exhibited significant improvements in the strength of the hip flexor, Semi-Tandem Stand, and Tandem Stand. Conclusion In this study, we developed an AIoT ergometer that delivered customized physical training prescriptions to improve the physical performance of long-term care facility residents. We believe that the application of AIFASE will help improve the quality of institutional care.

Altered glucose metabolism and its association with carbonic anhydrase 8 in Machado-Joseph Disease - Guan-Yu Lin; Chung-Yung Ma; Li-Chung Kuo; Benjamin Y. Hsieh; Hanbing Wang; Chin-San Liu; Mingli Hsieh (Metabolic Brain Disease, 2022)

Lactobacillus plantarum PS128 Promotes Intestinal Motility, Mucin Production, and Serotonin Signaling in Mice - Chih-Ming Chen; Chien-Chen Wu; Chin-Lin Huang; Min-Yu Chang; Shih-Hsuan Cheng; Ching-Ting Lin; Ying-Chieh Tsai (Probiotics and Antimicrobial Proteins, 2022)
Lactobacillus plantarum PS128 has been reported as a psychobiotic to improve mental health through the gut–brain axis in experimental animal models. To explore its mechanism of action in the gut, this study aimed to analyze the effects of L. plantarum PS128 ingestion on naïve and loperamide (Lop)-induced constipation mice. We found that, in the two mouse models, the weight, number, and water content of feces in the L. plantarum PS128 group were higher than those in the vehicle control group. Histological observation revealed that L. plantarum PS128 increased the level of colonic mucins including the major mucin MUC2. In addition, the charcoal meal test showed that L. plantarum PS128 significantly increased the small intestine transit in naïve mice, but not in the Lop-treated mice. Since intestinal serotonin has been found to modulate motility, we further analyzed the expression of genes related to serotonin signal transduction in the small intestine of naïve mice. The results showed that L. plantarum PS128 significantly altered the expression levels of Tph1 , Chga , Slc6a4 , and Htr4 , but did not affect the expression levels of Tph2 , Htr3a , and Maoa . Furthermore, immunohistochemistry revealed that L. plantarum PS128 significantly increased the number of serotonin-containing intestinal cells in mice. Taken together, our results suggest that L. plantarum PS128 could promote intestinal motility, mucin production, and serotonin signal transduction, leading to a laxative effect in mice.

Economic growth in selected G20 countries: How do different pollution emissions matter? - Thian-Hee Yiew; Chin-Yu Lee; Lin-Sea Lau (Environment, Development and Sustainability, 2021)

Collapsin response mediator protein 5 (CRMP5) modulates susceptibility to chronic social defeat stress in mice - Yu-Fen Lin; Kao Chin Chen; Yen Kuang Yang; Ya-Hsin Hsiao (Molecular Neurobiology, 2021)

New secondary metabolite with cytotoxicity from spawning soft coral Asterospicularia laurae in Taiwan - Jui-Hsin Su; Chih-I Liu; Mei-Chin Lu; Chi-I Chang; Min-Ying Hsieh; Yu-Chi Lin; Chang-Feng Dai; Ya-Han Zhang; Zheng-Yu Lin; Yun-Sheng Lin (Natural Product Research, 2021)

Natural polyketide 6-pentyl-2 H -pyrone-2-one and its synthetic analogues efficiently prevent marine biofouling - Mo Aqib Raza Khan; Bo-Wei Wang; Yih-Yu Chen; Ting-Hsuan Lin; Hsiu-Chin Lin; Yu-Liang Yang; Ka-Lai Pang; Chih-Chuang Liaw (Biofouling, 2021)

Continental shelf morphology controlled by bottom currents, mud diapirism, and submarine slumping to the east of the Gaoping Canyon, off SW Taiwan - Yi-Ching Yeh; Chung-Lin Tsai; Shu-Kun Hsu; Hsiao-Shan Lin; Kuan-Ting Chen; Yen-Yu Cho; Chin-Wei Liang (Geo-Marine Letters, 2021)

Improving Image Correlation and Differentiation of 3D Endoluminal Lesions in the Air Spaces Using a Novel Target Gray Level Mapping Technique: A Preliminary Study of Its Application to Computed Tomographic Colonography and Comparison with Traditional Surface Rendering Method - Lih-Shyang Chen; Ta-Wen Hsu; Shao-Jer Chen; Shu-Han Chang; Chih-Wen Lin; Yu-Ruei Chen; Chin-Chiang Hsieh; Shu-Chen Han; Ku-Yaw Chang; Chun-Ju Hou (Journal of Medical and Biological Engineering, 2020)

Optimizing the MIC breakpoints of amoxicillin and tetracycline for antibiotic selection in the rescue therapy of H. pylori with bismuth quadruple regimen - Ming-Tsung Hsieh; Wei-Lun Chang; Chung-Tai Wu; Hsiao-Bai Yang; Hsin-Yu Kuo; Meng-Ying Lin; Hsiu-Chi Cheng; Yu-Chin Tsai; Bor-Shyang Sheu (European Journal of Clinical Pharmacology, 2020)

Synergistic effects of pazopanib and hyperthermia against uterine leiomyosarcoma growth mediated by downregulation of histone acetyltransferase 1 - Chiao-Yun Lin; Angel Chao; Ren-Chin Wu; Li-Yu Lee; Shir-Hwa Ueng; Chia-Lung Tsai; Yun-Shien Lee; Meng-Ting Peng; Lan-Yan Yang; Huei-Jean Huang; Hsin-Shih Wang; Chyong-Huey Lai (Journal of Molecular Medicine, 2020)

Reconnaissance and learning after the February 6, 2018, earthquake in Hualien, Taiwan - Jui-Liang Lin; Chun-Hsiang Kuo; Yu-Wen Chang; Shu-Hsien Chao; Yi-An Li; Wen-Cheng Shen; Chung-Han Yu; Cho-Yen Yang; Fan-Ru Lin; Hsiao-Hui Hung; Chun-Chung Chen; Chin-Kuo Su; et al. (Bulletin of Earthquake Engineering, 2020)

Combined effect of polymorphisms of MTHFR and MTR and arsenic methylation capacity on developmental delay in preschool children in Taiwan - Yu-Mei Hsueh; Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Horng-Sheng Shiue; Ssu-Ning Chien; Chih-Ying Lee; Ming-I. Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2020)

Therapeutic Efficacy of Subcutaneous and Intraperitoneal Injections of a Single Dose of Human Umbilical Mesenchymal Stem Cells in Acute and Chronic Colitis in a Mouse Model - Yu-Lung Chang; Huei-Yu Lo; Shun-Ping Cheng; Kuo-Ting Chang; Xiu-Fang Lin; Sheng-Ping Lee; Jason Ma; Ming-Ling Kuo; Ming-Fa Hsieh; Chin-Kan Chan (Journal of Medical and Biological Engineering, 2020)

A full-scale study of external circulation sludge bed (ECSB) system for anaerobic wastewater treatment in a whiskey distillery - Yu-Chung Lin; Chen-Hua Ni; Chin-Yi Wu; Justin Chun-Te Lin (Environmental Science and Pollution Research, 2019)

Hydro-mechanical response with respect to the air ventilation for water filtration in homogeneous soil - Wei-Lin Lee; Yih-Chin Tai; Chjeng-Lun Shieh; Kuniaki Miyamoto; Yu-Feng Lin (Journal of Mountain Science, 2019)

Association of plasma folate, vitamin B12 levels, and arsenic methylation capacity with developmental delay in preschool children in Taiwan - Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Pui-Lam Ao; Horng-Sheng Shiue; Shiau-Rung Huang; Chien-Tien Su; Ming-I Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2019)

PARK14 (D331Y) PLA2G6 Causes Early-Onset Degeneration of Substantia Nigra Dopaminergic Neurons by Inducing Mitochondrial Dysfunction, ER Stress, Mitophagy Impairment and Transcriptional Dysregulation in a Knockin Mouse Model - Ching-Chi Chiu; Chin-Song Lu; Yi-Hsin Weng; Ying-Ling Chen; Ying-Zu Huang; Rou-Shayn Chen; Yi-Chuan Cheng; Yin-Cheng Huang; Yu-Chuan Liu; Szu-Chia Lai; Kun-Jun Lin; Yan-Wei Lin; et al. (Molecular Neurobiology, 2019)

Recombinant FGF21 Protects Against Blood-Brain Barrier Leakage Through Nrf2 Upregulation in Type 2 Diabetes Mice - Zhanyang Yu; Li Lin; Yinghua Jiang; Ian Chin; Xiaojie Wang; Xiaokun Li; Eng H. Lo; Xiaoying Wang (Molecular Neurobiology, 2019)

The combination of everolimus and terameprocol exerts synergistic antiproliferative effects in endometrial cancer: molecular role of insulin-like growth factor binding protein 2 - Angel Chao; Chiao-Yun Lin; Ren-Chin Wu; Yun-Shien Lee; Li-Yu Lee; Chia-Lung Tsai; Lan-Yan Yang; Hsuan Liu; Shu-Jen Chen; Tzu-Hao Wang; Chyong-Huey Lai (Journal of Molecular Medicine, 2018)

Detection, sequence analysis, and antibody prevalence of porcine deltacoronavirus in Taiwan - Tien-Huan Hsu; Hao-Ping Liu; Chieh-Yu Chin; Chinling Wang; Wan-Zhen Zhu; Bing-Lin Wu; Yu-Chung Chang (Archives of Virology, 2018)

Clinical and microbiological characteristics of peritoneal dialysis-related peritonitis caused by Escherichia coli in southern Taiwan - Wei-Hung Lin; Chin-Chung Tseng; An-Bang Wu; Yu-Tzu Chang; Te-Hui Kuo; Jo-Yen Chao; Ming-Cheng Wang; Jiunn-Jong Wu (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Antiviral prophylaxis during chemotherapy or immunosuppressive drug therapy to prevent HBV reactivation in patients with resolved HBV infection: a systematic review and meta-analysis - Yi-Chia Su; Pei-Chin Lin; Hsien-Chung Yu; Chih-Chien Wu (European Journal of Clinical Pharmacology, 2018)

Geochronological and geochemical constraints on the origin of the Southeast Anatolian ophiolites, Turkey - A. Feyzi Bingöl; Melahat Beyarslan; Yu-Chin Lin; Hao-Yang Lee (Arabian Journal of Geosciences, 2018)

Sodium Metabisulfite: Effects on Ionic Currents and Excitotoxicity - Ming-Chi Lai; Te-Yu Hung; Kao-Min Lin; Pi-Shan Sung; Shyh-Jong Wu; Chih-Sheng Yang; Yi-Jen Wu; Jing-Jane Tsai; Sheng-Nan Wu; Chin-Wei Huang (Neurotoxicity Research, 2018)

Extension of C. elegans lifespan using the ·NO-delivery dinitrosyl iron complexes - Hsiao-Wen Huang; Yen-Hung Lin; Min-Hsuan Lin; Ya-Rong Huang; Chih-Hung Chou; Hsiao-Chin Hong; Mei-Ren Wang; Yu-Ting Tseng; Po-Chun Liao; Min-Chuan Chung; Yu-Jie Ma; Shou-Cheng Wu; et al. (JBIC Journal of Biological Inorganic Chemistry, 2018)

Treatment outcome of non-carbapenemase-producing carbapenem-resistant Klebsiella pneumoniae infections: a multicenter study in Taiwan - Chin-Fang Su; Chien Chuang; Yi-Tsung Lin; Yu-Jiun Chan; Jung-Chung Lin; Po-Liang Lu; Ching-Tai Huang; Jann-Tay Wang; Yin-Ching Chuang; L. Kristopher Siu; Chang-Phone Fung (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

IL-28 and IL-29 as protective markers in subject with dengue fever - Chih-Hsing Hung; Chung-Hao Huang; Lin Wang; Chun-Chi Huang; Meng-Chieh Wu; Yi-Ying Chin; Chun-Yu Lin; Ko Chang; Deng-Chyang Wu; Yen-Hsu Chen (Medical Microbiology and Immunology, 2017)

p-Hydroxyacetophenone suppresses nuclear factor-κB-related inflammation in nociceptive and inflammatory animal models - Chang Ching-Wen; Chen Yun-Chieh; Lin Yu-Chin; Peng Wen-Huang (Journal of Natural Medicines, 2017)

Beneficial Effect of Astragaloside on Alzheimer’s Disease Condition Using Cultured Primary Cortical Cells Under β-amyloid Exposure - Ching-Ping Chang; Yu-Fan Liu; Hung-Jung Lin; Chien-Chin Hsu; Bor-Chih Cheng; Wen-Pin Liu; Mao-Tsun Lin; Shu-Fen Hsu; Li-Sheng Chang; Kao-Chang Lin (Molecular Neurobiology, 2016)

One-step reverse transcription loop-mediated isothermal amplification for the detection of Capsicum chlorosis virus in Phalaenopsis orchids - Cheng-Ping Kuan; Yu-Fei Lin; Yu-Chun Lin; Chin-Chih Chen (Journal of General Plant Pathology, 2016)

The modulation of Th2 immune pathway in the immunosuppressive effect of human umbilical cord mesenchymal stem cells in a murine asthmatic model - Chin-Kan Chan; Ting-Chun Lin; Yung-An Huang; Ya-Shan Chen; Chia-Ling Wu; Huei-Yu Lo; Ming-Ling Kuo; Kang-Hsi Wu; Jing-Long Huang (Inflammation Research, 2016)

Polymorphisms of human 8-oxoguanine DNA glycosylase 1 and 8-hydroxydeoxyguanosine increase susceptibility to arsenic methylation capacity-related urothelial carcinoma - Chao-Yuan Huang; Yeong-Shiau Pu; Horng-Sheng Shiue; Wei-Jen Chen; Ying-Chin Lin; Yu-Mei Hsueh (Archives of Toxicology, 2016)

Quantitative measurement of Parkinsonian gait from walking in monocular image sequences using a centroid tracking algorithm - Sheng-Huang Lin; Shih-Wei Chen; Yu-Chun Lo; Hsin-Yi Lai; Chich-Haung Yang; Shin-Yuan Chen; Yuan-Jen Chang; Chin-Hsing Chen; Wen-Tzeng Huang; Fu-Shan Jaw; You-Yin Chen; Siny Tsang; et al. (Medical & Biological Engineering & Computing, 2016)

Development of single-chain variable fragments (scFv) against influenza virus targeting hemagglutinin subunit 2 (HA2) - Tai-Wei Li; Shu-Fang Cheng; Yen-Tzu Tseng; Yu-Chih Yang; Wen-chun Liu; Sheng-Cyuan Wang; Mei-Ju Chou; Yu-Jen Lin; Yueh Wang; Pei-Wen Hsiao; Suh-Chin Wu; Ding-Kwo Chang (Archives of Virology, 2016)

Dysfunction Screening in Experimental Arteriovenous Grafts for Hemodialysis Using Fractional-Order Extractor and Color Relation Analysis - Ming-Jui Wu; Wei-Ling Chen; Chung-Dann Kan; Fan-Ming Yu; Su-Chin Wang; Hsiu-Hui Lin; Chia-Hung Lin (Cardiovascular Engineering and Technology, 2015)

Physical regulation of stem cells differentiation into teno-lineage: current strategies and future direction - Jia Lin Chen; Wei Zhang; Ze Yu Liu; Boon Chin Heng; Hong Wei Ouyang; Xue Song Dai (Cell and Tissue Research, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Association Study Between Macrophage Migration Inhibitory Factor-173 Polymorphism and Acute Myeloid Leukemia in Taiwan - Latha Ramireddy; Chien-Yu Lin; Su-Ching Liu; Wan-Yu Lo; Rouh-Mei Hu; Yi-Chin Peng; Ching-Tien Peng (Cell Biochemistry and Biophysics, 2014)

Spatial distribution of soil erosion and suspended sediment transport rate for Chou-Shui river basin - Chin-Ping Lin; Ching-Nuo Chen; Yu-Min Wang; Chih-Heng Tsai; Chang-Tai Tsai (Journal of Earth System Science, 2014)

Two Frequent Mutations Associated with the Classic Form of Propionic Acidemia in Taiwan - Yen-Hui Chiu; Yu-Ning Liu; Wei-Ling Liao; Ying-Chen Chang; Shuan-Pei Lin; Chia-Chi Hsu; Pao-Chin Chiu; Dau-Ming Niu; Chung-Hsing Wang; Yu-Yuan Ke; Yin-Hsiu Chien; Kwang-Jen Hsiao; et al. (Biochemical Genetics, 2014)

MicroRNA-30c serves as an independent biochemical recurrence predictor and potential tumor suppressor for prostate cancer - Xiao-hui Ling; Zhao-dong Han; Dan Xia; Hui-chan He; Fu-neng Jiang; Zhuo-yuan Lin; Xin Fu; Ye-han Deng; Qi-shan Dai; Chao Cai; Jia-hong Chen; Yu-xiang Liang; et al. (Molecular Biology Reports, 2014)

Genetic variations in TP53 binding sites are predictors of clinical outcomes in prostate cancer patients - Victor C. Lin; Chao-Yuan Huang; Yung-Chin Lee; Chia-Cheng Yu; Ta-Yuan Chang; Te-Ling Lu; Shu-Pin Huang; Bo-Ying Bao (Archives of Toxicology, 2014)

BDNF and Exercise Enhance Neuronal DNA Repair by Stimulating CREB-Mediated Production of Apurinic/Apyrimidinic Endonuclease 1 - Jenq-Lin Yang; Yu-Ting Lin; Pei-Chin Chuang; Vilhelm A. Bohr; Mark P. Mattson (NeuroMolecular Medicine, 2014)

Telbivudine and adefovir combination therapy for patients with chronic lamivudine-resistant hepatitis B virus infections - Ming-Tsung Lin; Yeh-Pin Chou; Tsung-Hui Hu; Hsien-Chung Yu; Yu-Chun Hsu; Ming-Chao Tsai; Po-Lin Tseng; Kuo-Chin Chang; Yi-Hao Yen; King-Wah Chiu (Archives of Virology, 2014)

Hyperinakin, a new anti-inflammatory phloroglucinol derivative from Hypericum nakamurai - Yuan-Bin Cheng; Ahmed Eid Fazary; Yu-Chi Lin; I-Wen Lo; Seow-Chin Ong; Shun-Ying Chen; Ching-Te Chien; Yen-Jung Lin; Wan-Wan Lin; Ya-Ching Shen (Natural Product Research, 2013)

β2-Glycoprotein I inhibits VEGF-induced endothelial cell growth and migration via suppressing phosphorylation of VEGFR2, ERK1/2, and Akt - Wen-Chin Chiu; Jan-Yu Lin; Tzong-Shyuan Lee; Li-Ru You; An-Na Chiang (Molecular and Cellular Biochemistry, 2013)

Protection by chrysin, apigenin, and luteolin against oxidative stress is mediated by the Nrf2-dependent up-regulation of heme oxygenase 1 and glutamate cysteine ligase in rat primary hepatocytes - Chin-Shiu Huang; Chong-Kuei Lii; Ai-Hsuan Lin; Yu-Wen Yeh; Hsien-Tsung Yao; Chien-Chun Li; Tsu-Shing Wang; Haw-Wen Chen (Archives of Toxicology, 2013)

Interplay of RsbM and RsbK controls the σ B activity of Bacillus cereus - Lei‐Chin Chen; Jung‐Chi Chen; Jwu‐Ching Shu; Chien‐Yen Chen; Ssu‐Ching Chen; Shu‐Hwa Chen; Chun‐Yen Lin; Chi‐Yu Lu; Chien‐Cheng Chen (Environmental Microbiology, 2012)
Summary The alternative transcription factor σ B of Bacillus cereus controls the expression of a number of genes that respond to environmental stress. Four proteins encoded in the sigB gene cluster, including RsbV, RsbW, RsbY (RsbU) and RsbK, are known to be essential in the σ B ‐mediated stress response. In the context of stress, the hybrid sensor kinase RsbK is thought to phosphorylate the response regulator RsbY, a PP2C serine phosphatase, leading to the dephosphorylation of the phosphorylated RsbV. The unphosphorylated RsbV then sequesters the σ B antagonist, RsbW, ultimately liberating σ B . The gene arrangement reveals an open reading frame, bc1007 , flanked immediately downstream by rsbK within the sigB gene cluster. However, little is known about the function of bc1007 . In this study, the deletion of bc1007 resulted in high constitutive σ B expression independent of environmental stimuli, indicating that bc1007 plays a role in σ B regulation. A bacterial two‐hybrid analysis demonstrated that BC1007 interacts directly with RsbK, and autoradiographic studies revealed a specific C 14 ‐methyl transfer from the radiolabelled S‐adenosylmethionine to RsbK when RsbK was incubated with purified BC1007. Our data suggest that BC1007 (RsbM) negatively regulates σ B activity by methylating RsbK. Additionally, mutagenic substitution was employed to modify 12 predicted methylation residues in RsbK. Certain RsbK mutants were able to rescue σ B activation in a rsbK ‐deleted bacterial strain, but RsbK E439A failed to activate σ B , and RsbK E446A only moderately induced σ B . These results suggest that Glu439 is the preferred methylation site and that Glu446 is potentially a minor methylation site. Gene arrays of the rsbK orthologues and the neighbouring rsbM orthologues are found in a wide range of bacteria. The regulation of sigma factors through metylation of RsbK‐like sensor kinases appears to be widespread in the microbial world.

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Elevated risk of hypertension induced by arsenic exposure in Taiwanese rural residents: possible effects of manganese superoxide dismutase (MnSOD) and 8-oxoguanine DNA glycosylase (OGG1) genes - Shiuan-Chih Chen; Chun-Chieh Chen; Chung-Yih Kuo; Chun-Huang Huang; Chin-Hsiu Lin; Zi-Yun Lu; Yi-Yu Chen; Hong-Shen Lee; Ruey-Hong Wong (Archives of Toxicology, 2012)

Availability of dopamine and serotonin transporters in opioid-dependent users—a two-isotope SPECT study - Tzung Lieh Yeh; Kao Chin Chen; Shih-Hsien Lin; I. Hui Lee; Po See Chen; Wei Jen Yao; Sheng-Yu Lee; Yen Kuang Yang; Ru-Band Lu; Mei-Hsiu Liao; Nan-Tsing Chiu (Psychopharmacology, 2012)

Identification of secretory gelsolin as a plasma biomarker associated with distant organ metastasis of colorectal cancer - Ming-Hung Tsai; Chih-Ching Wu; Pei-Hua Peng; Ying Liang; Yung-Chin Hsiao; Kun-Yi Chien; Jeng-Ting Chen; Shin-Jie Lin; Rei-Ping Tang; Ling-Ling Hsieh; Jau-Song Yu (Journal of Molecular Medicine, 2012)

Lipopolysaccharide-stimulated activation of murine DC2.4 cells is attenuated by n-butylidenephthalide through suppression of the NF-κB pathway - Ru-Huei Fu; Horng-Jyh Hran; Ching-Liang Chu; Chin-Mao Huang; Shih-Ping Liu; Yu-Chi Wang; Ya-Hsien Lin; Woei-Cherng Shyu; Shinn-Zong Lin (Biotechnology Letters, 2011)

Molecular epidemiology of Echovirus 30 in Taiwan, 1988–2008 - Guan-Ming Ke; Kuei-Hsiang Lin; Po-Liang Lu; Yi-Chin Tung; Chu-Feng Wang; Liang-Yin Ke; Min-Sheng Lee; Pei-Chin Lin; Hui-Ju Su; Yi-Ying Lin; Tzu-Ping Huang; Jen-Ren Wang; et al. (Virus Genes, 2011)

Anti-herpes simplex virus effects of berberine from Coptidis rhizoma, a major component of a Chinese herbal medicine, Ching-Wei-San - Lengsu William Chin; Yu-Wen Cheng; Shih-Shen Lin; Ya-Yun Lai; Long-Yau Lin; Ming-Yung Chou; Ming-Chih Chou; Chi-Chiang Yang (Archives of Virology, 2010)

The changes in different ozone metrics and their implications following precursor reductions over northern Taiwan from 1994 to 2007 - Yu-Kai Lin; Ta-Hsiung Lin; Shuenn-Chin Chang (Environmental Monitoring and Assessment, 2010)

Constitutive expression of a fungal glucose oxidase gene in transgenic tobacco confers chilling tolerance through the activation of antioxidative defence system - Subbiyan Maruthasalam; Yi Lun Liu; Ching Mei Sun; Pei Ying Chen; Chih Wen Yu; Pei Fang Lee; Chin Ho Lin (Plant Cell Reports, 2010)

Regeneration of soybean (Glycine max L. Merrill) through direct somatic embryogenesis from the immature embryonic shoot tip - Murugan Loganathan; Subbiyan Maruthasalam; Ling Yin Shiu; Wei Ching Lien; Wen Hwei Hsu; Pei Fang Lee; Chih Wen Yu; Chin Ho Lin (In Vitro Cellular & Developmental Biology - Plant, 2010)

Recombinant ORF66 and ORFK12 antigens for the detection of human herpesvirus 8 antibodies in HIV-positive and -negative patients - Tsuey-Ching Yang; Chun-Pin Chang; Yu-Ching Lan; Chao-Li Liu; Mu-Chin Shih; Fang-Yang Wu; Cheng-Wen Lin (Biotechnology Letters, 2009)

Complete sequence of a subgroup 3.4 strain of classical swine fever virus from Taiwan - Yu-Ju Lin; Maw-Sheng Chien; Ming-Chung Deng; Chin-Cheng Huang (Virus Genes, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Effect of Epstein–Barr virus infection on global gene expression in nasopharyngeal carcinoma - Yuan-Chii Gladys Lee; Yu-Chyi Hwang; Kuang-Chi Chen; Yong-Shiang Lin; Dah-Yeou Huang; Tao-Wei Huang; Cheng-Yan Kao; Han-Chung Wu; Chin-Tarng Lin; Chi-Ying F. Huang (Functional & Integrative Genomics, 2006)

The effect of salinity on trichloroethylene co-metabolism by mixed cultures enriched on phenol - Chi-Yuan Lee; Yu-Chia Chan; Chin-Lung Lin (World Journal of Microbiology and Biotechnology, 2005)

Aviglycine and propargylglycine inhibit conidial germination and mycelial growth of Fusarium oxysporumf. sp. luffae - Jung-Kang Jin; Douglas O. Adams; Yeong Ko; Chih-Wen Yu; Chin-Ho Lin (Mycopathologia, 2004)